(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2013)
The article discusses a number of historical cases of nations that have developed anti-miscegenation laws premised on a logic of “state mixophobia”, with instances as diverse as the Spanish colonization of the Americas and later of Equatorial Guinea; England and Australia during the colonial and postcolonial eras; the United States in the nineteenth and twentieth centuries; Germany during the Nazi period; and South Africa under apartheid. I argue that in all of these cases, hybridity represented not so much the danger of external enemies, but rather the destruction of internal borders: that is, a threat to the socio-political and economic status quo. This historical-anthropological analysis can help us in today’s world to better understand and reflect critically on the social, political, and economic contexts in which reductionist views of hybridity emerge and are used to legitimize social systems of exclusion.